From radial head to radiocapitellar to total elbow replacement: A case report. (2015) - Hackl, Michael; Burkhart, Klaus Josef; Wegmann, Kilian; Hollinger, Boris; Lichtenberg, Sven; Müller, Lars Peter
Highlights: Overstuffing is a serious yet avoidable complication of radial head arthroplasty. Overstuffing severely alters elbow joint kinematics and leads to capitellar erosion. Radiocapitellar arthroplasty can be a salvage procedure in such cases. Limited clinical data is available thus far regarding radiocapitellar arthroplasty. The possibility for early failure due to ulnohumeral erosion has to be considered. Abstract: Introduction: Radiocapitellar arthroplasty represents a possible treatment option for isolated osteoarthritis of the radial column. We report the first case of early failure of this procedure. Presentation of case: We present the case of a 41-year old male who sustained a terrible triad injury to his right elbow and subsequently underwent radial head arthroplasty. Due to overstuffing of the radial head prosthesis, capitellar erosion occurred and radiocapitellar arthroplasty was thus performed. Only one year later, conversion of the radiocapitellar replacement to total elbow arthroplasty was required as a result of progressive ulnohumeral osteoarthritis. Discussion: According to the currently limited clinical data, radiocapitellar arthroplasty provides satisfactory results. However, biomechanical analysis shows that available prostheses do not sufficiently reproduce the radiocapitellar anatomy. The design of the prosthesis might thus have contributed to the rapid progression of ulnohumeral erosion following radiocapitellar arthroplasty although the poor outcome may also be attributed to the trauma itself along with the inadequate initial treatment. Conclusions: The indication for radiocapitellar arthroplasty warrants careful consideration given the results of biomechanical analysis and the early failure due to progressive ulnohumeral erosion seen in the present case.